Yield Attributes and Biochemical Compositions of Elites and Landraces of Pigeon Pea [Cajanus cajan (L.) Millsp] - DAUDU, O.A.Y (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
Pigeon pea (Cajanus cajan L. Millsp.) is an important grain legume grown mostly in the tropical regions of the world, Nigeria inclusive. The crop is still underutilised in Nigeria; the potentials of the crop in terms of yield traits and biochemical compositions, with ability of enhancing food security and preventing over-dependent on very expensive animal protein, is yet to be fully exploited. It was based on this premise that this study was designed. A total of twenty-five accessions were obtained from International Institute of Tropical Agriculture, lbadan; National Centre for Genetic Resources and Biotechnology, Ibadan and Local farmers in Oyo state, Nigeria. The seeds of the accession were sown in the field in a Randomised Complete Block Design (RCBD) with three replicates. Standard procedures were followed for determination of yield parameters as well as biochemical compositions. It showed that NG/SA/11/08/108 produced the highest grain yield (437.00). Similarly, TCC-8126 produced the highest crude protein (22.53 %) while PG/OY/18/002 had the highest carbohydrate contents (52.22 %). TCC-8126 was the best elite genotype in terms of amino acid profile, containing glutamic acid (18.10 %), aspartic acid (11.4 %); arginine (7.41 %), alanine (5.90 %). The values produced for both nutritional compositions and amino acid profiles were within the recommended standard limits set by Food and Agriculture Organisation and United States Department of Agriculture. NG/SA/11/08/108, NG/AO/MAY/09/021/02, TCC-151, TCC-8126, TT-8129 and TCC-2 have been selected as promising genotypes that could serve as breeding lines for future breeding programme of Cajanus cajan in Nigeria.